Micro-PET/CT Monitoring of Herpes Thymidine Kinase Suicide Gene Therapy in a Prostate Cancer Xenograft: The Advantage of a Cell-specific Transcriptional Targeting Approach - Mai Johnson; Makoto Sato; Jeremy Burton; Sanjiv S. Gambhir; Michael Carey; Lily Wu (Molecular Imaging, 2005)
Cancer gene therapy based on tissue-restricted expression of cytotoxic gene should achieve superior therapeutic index over an unrestricted method. This study compared the therapeutic effects of a highly augmented, prostate-specific gene expression method to a strong constitutive promoter-driven approach. Molecular imaging was coupled to gene therapy to ascertain real-time therapeutic activity. The imaging reporter gene (luciferase) and the cytotoxic gene (herpes simplex thymidine kinase) were delivered by adenoviral vectors injected directly into human prostate tumors grafted in SCID mice. Serial bioluminescence imaging, positron emission tomography, and computed tomography revealed restriction of gene expression to the tumors when prostate-specific vector was employed. In contrast, administration of constitutive active vector resulted in strong signals in the liver. Liver serology, tissue histology, and frail condition of animals confirmed liver toxicity suffered by the constitutive active cohorts, whereas the prostate-targeted group was unaffected. The extent of tumor killing was analyzed by apoptotic staining and human prostate marker (prostate-specific antigen). Overall, the augmented prostate-specific expression system was superior to the constitutive approach in safeguarding against systemic toxicity, while achieving effective tumor killing. Integrating noninvasive imaging into cytotoxic gene therapy will provide a useful strategy to monitor gene expression and therapeutic efficacy in future clinical protocols.